2014
DOI: 10.1134/s0006297914120037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular barriers to processes of genetic reprogramming and cell transformation

Abstract: Genetic reprogramming by ectopic expression of transcription factor genes induces the pluripotent state in somatic cells. This technology provides an opportunity to establish pluripotent stem cells for each person, as well as to get better understanding of epigenetic mechanisms controlling cell state. Interestingly, some of the molecular processes that accompany somatic cell reprogramming in vitro are also characteristic for tumor manifestation. Thus, similar "molecular barriers" that control the stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Nowadays, stem cell research becomes the hot topic to the researchers because stem cells have the ability to self-renew and differentiate into various kinds of cells [ 4 ]. Current research suggests that genetic reprogramming may play a potential role in stem/cancer stem cell biology, by sustaining the pluripotency of stem cells (SCs) and increasing their differentiation into mature cell populations [ 5 , 6 ]. Studies have shown that dysplastic growth could be induced by the ectopic expression of stemness marker genes in adult epithelial tissues [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, stem cell research becomes the hot topic to the researchers because stem cells have the ability to self-renew and differentiate into various kinds of cells [ 4 ]. Current research suggests that genetic reprogramming may play a potential role in stem/cancer stem cell biology, by sustaining the pluripotency of stem cells (SCs) and increasing their differentiation into mature cell populations [ 5 , 6 ]. Studies have shown that dysplastic growth could be induced by the ectopic expression of stemness marker genes in adult epithelial tissues [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%